Effect of ethofumesate herbicide on energy metabolism in roach (Rutilus rutilus) - V. Maes; A. Vettier; O. Dedourge-Geffard; A. Geffard; S. Paris-Palacios; S. Betoulle; E. David (MDPI AG, 2014)
Not available